The Information Service in Developing the Students’ Discipline Associated to the Utilization of School Canteen - Andrian Novialdi; Prayitno Prayitno; Marjohan Marjohan (International Journal of Applied Counseling and Social Sciences, 2019)
This research begins from the condition of students’ discipline associated to the utilization of school canteen. The aim of the research is to obtain an overview regarding the information services provided by the guidance and counseling teachers. The background of the research is about the students’ discipline associated to school canteen, condition and role of school canteen and also the role of guidance and counseling service particularly information service. The research used a descriptive quantitative method. Then, the population was the principal, guidance and counseling teachers, and students in Padang City Vocational School who were selected by using the purposive sampling technique. The research findings are: 1) the condition and role of school stalls according to the opinion of principal are in good category and according to the opinion of guidance and counseling teachers are in good enough category. 2) Students' disciplin in the utilization of school canteen according to the opinion of guidance and counseling teachers are good, meanwhile the student' opinions  are good enough category. 3) The implementation of information services associated to the utilization of school canteens according to guidance and counseling teachers and students is in the good category.